ANALISIS DETERMINAN REALISASI PENANAMAN MODAL ASING DI INDONESIA PERIODE 2000Q1:2022Q4 - Ramadhan, Muhammad Arvenda; Sitorus, Nurbetty Herlina (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2023)
As a developing country, foreign investment plays an important role in developing the economy in Indonesia. It can increase economic growth, create jobs, and open up pathways for the transfer of technology and knowledge from abroad. This study aims to examine the factors that can affect the realization of foreign investment in Indonesia. The variables that will be used in the analysis of this study consist of foreign investment realization, economic growth rate, natural resources, labor force and real exchange rate. This research will use the Error Correction Model method as a research analysis tool. According to the results of short-term analysis, natural resources can affect the realization of foreign investment into Indonesia positively and significantly. In addition, real exchange rate depreciation can also encourage an increase in realized foreign investment in Indonesia. According to the results of long-term analysis, economic growth rate, natural resources, labor force and real exchange rate are known to have a significant positive influence on the realization of foreign investment in Indonesia.